Violence in Colombia complex problem that demands emergency solutions from education - Castillo, América (2019)
Understand the violence in Colombia which comes from the armed conflict as a complex problem of education, in perspective of emerging archetypes for territorial management, as a commitment of humanity around three crucial issues: the influence of rural and urban education by violence; deschooling and forced displacement; since being a teacher is a matter of hero. In relation to this we must mention that through the Peace Agreements between the National Government and the Revolutionary Armed Forces of Colombia (FARC), public policies, government programs, demands and actions of society have generated powerful power constitutional bodies and expressions of governance and governance, for the importance of different realities lived in the territories of our country and that have supported over five decades, the scourge of violence by groups outside the law. A methodologically commitment addressed through the review of explicit sources in Centro de Memoria Histórica (The Historical Memory Centre), accompanied by reflections and interpretations of partial results.